PEMANFAATAN MEDIA VIRTUAL REALITY UNTUK MENINGKATKAN PEMAHAMAN KONSEP SAINS PADA ANAK USIA DINI - Mesa Pramasela; Sefriyanti, Sefriyanti (LPPM STAI DARUSSALAM LAMPUNG, 2025)
Abstract: The use of innovative and interactive learning media is an urgent need in the digital era, especially in early childhood education, to overcome the challenges of understanding science concepts that are often abstract and difficult to understand. Virtual reality (VR) offers an immersive learning experience, providing opportunities to increase student engagement and deepen conceptual understanding. This study aims to analyze the effectiveness of using VR media in improving understanding of science concepts in early childhood. The research method uses a quantitative approach with a quasi-experimental design, involving 30 early age group students as samples, which are divided into control and experimental groups. The results of the study showed that students who learned using VR media experienced a significant increase in understanding of science concepts compared to students who used conventional learning methods. VR media has been proven to be able to attract students' attention, increase interaction, and help visualize abstract concepts in a concrete way. The implications of this study indicate that the integration of VR in early childhood learning can be an effective strategy to support more meaningful science learning. Keywords: Virtual Reality Media; Understanding Science Concepts; Early Childhood